Analisis Produktivitas pada Unit Produksi dengan Metode Objective Matrix (OMAX) di CV. Serba Jaya Oke Surabaya - Destalia, Riris; Aryanny, Enny (BRILIANT: Jurnal Riset dan Konseptual, 2025)
CV. Serba Jaya Oke is a manufacturing company engaged in the production of plastic household appliances. In its operations, the company experienced difficulties in achieving production targets. This research was conducted to analyze the productivity of production units from January to December 2023 to understand partial productivity levels and develop recommendations for improvement. The methods in this research are objective matrix (OMAX), analytical hierarchy process (AHP), traffic light system, fishbone diagram, and 5W+1H. From this research, it is known that the highest productivity index value was in August 2023, namely 311,2%, while the lowest value occurred in December 2023 with a productivity index of -82,9%. Suggestions for improvement were given to the five productivity measurement criteria because these criteria had poor scores in certain periods. By applying this method, companies can increase partial productivity and identify triggers for decreased productivity in certain periods.